Pengaruh Pembelajaran Berdiferensiasi terhadap Motivasi Belajar Siswa dalam Pembelajaran Sejarah - Rifa Shania Ramdhani; Didin Sarifudin; Wawan Darmawan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The diverse characters and abilities of students mean that every teacher must be able to think creatively in designing learning that takes into account the diversity of students. This is done so that the resulting learning is able to meet the learning needs of each student so that the expected learning objectives can be achieved. One type of learning that can meet students' learning needs is differentiation learning. The aim of this research is to determine the effect of differentiated learning on students' learning motivation in learning history. This research uses a Quasi Experimental research method with a non-equivalent group design (Pre-test and Post-test). The population and research sample chosen in this study was SMA Negeri 10 Tasikmalaya, class XI-8 as the experimental class and class XI-9 as the control class. The results of the research show that the average N-gain value of learning motivation in the experimental class is 0.47 in the medium category and the average N-gain value in the control class is 0.13 in the low category. Based on the results of these values, it shows that there is student learning motivation after being treated with differentiated learning in history learning, meaning that it can be concluded that there is an influence of differentiated learning on students' learning motivation in history learning.